СОЦИАЛНО МРЕЖОВИ АНАЛИЗ И ОПТИМИЗАЦИЯ НА БИЗНЕС ПРОЦЕСИ - Ivanova, Antonina (E-Journal VFU, 2024)
The purpose of the article is to make a connection between the method of social network analysis and the optimization of business processes. The conceptual apparatus in the areas of social network analysis and business processes is specified. Applications of social network analysis in business are described. A social network survey was conducted and proposals were made for the optimization of business processes
Keywords: social network analysis; business process; business process management; business process optimization; metrics; NodeXL